Stability of C3 and C4 Grass Patches in Woody Encroached Rangeland after Fire and Simulated Grazing - R. James Ansley; William E. Pinchak (Diversity, 2023)
As the woody legume, Prosopis glandulosa (honey mesquite) has encroached into grasslands and rangelands in the southern Great Plains, USA, two grass species, C4 shortgrass, Buchloe dactyloides (buffalograss), and C3 mid-grass, Nassella leucotricha (Texas wintergrass), have increased in dominance. Occurrence of more productive C4 mid-grasses and herbaceous diversity have declined. We measured effects of various combinations of spring clipping (to simulate cattle grazing) and summer and/or winter fire treatments on the stability of monoculture patches of these two grass species over an eight-year period, with the goal of reducing Nassella and increasing C4 mid-grass cover. All fire treatments top-killed most Prosopis trees that subsequently resprouted. Buchloe cover declined in the No Clip + No Fire treatment but remained intact with clipping and/or fire. Frequent clipping reduced Nassella cover across all fire treatments. Buchloe encroachment into Nassella patches was greatest in the Clip + Alternate Season fire treatment. C4 mid-grass cover increased to 15–25% in Nassella patches in several fire-only or Clip + Fire treatments; greatest gains were observed in treatments that included summer fire. In contrast, C4 mid-grass gains were lower in Buchloe patches. These results suggest that C4 mid-grass restoration was linked with treatments that reduced Nassella cover.